2016
DOI: 10.1111/dmcn.13040
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal ischemia deteriorates white matter, brain organization, and function: implications for prematurity and cerebral palsy

Abstract: Cerebral palsy (CP) describes a group of neurodevelopmental disorders of posture and movement that are frequently associated with sensory, behavioral, and cognitive impairments. The clinical picture of CP has changed with improved neonatal care over the past few decades, resulting in higher survival rates of infants born very preterm. Children born preterm seem particularly vulnerable to perinatal hypoxia-ischemia insults at birth. Animal models of CP are crucial for elucidating underlying mechanisms and for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 50 publications
1
44
0
1
Order By: Relevance
“…Significant loss of the progenitor pool and gross reductions in the number of myelinating OLs underlies the maturation blockade seen with injury. Apneic, ischemic, and inflammatory events cause a delay maturation of neuronal and glial cell populations, and diffuse abnormalities in WM that result in a reduced capacity to synthesize myelin [46,164]. Accordingly, the resultant diffuse WM injury is believed to be a major cause of disability in survivors [165].…”
Section: Encephalopathy Of Prematuritymentioning
confidence: 99%
“…Significant loss of the progenitor pool and gross reductions in the number of myelinating OLs underlies the maturation blockade seen with injury. Apneic, ischemic, and inflammatory events cause a delay maturation of neuronal and glial cell populations, and diffuse abnormalities in WM that result in a reduced capacity to synthesize myelin [46,164]. Accordingly, the resultant diffuse WM injury is believed to be a major cause of disability in survivors [165].…”
Section: Encephalopathy Of Prematuritymentioning
confidence: 99%
“…Thus, both LPS injections and asphyxia procedure used in the present study may have caused reactive astrogliosis, which could explain the increase observed in the number of glial cells in the primary somatosensory cortex and striatum (Haupt et al, 2007;Pekny et al, 2014). On the other hand, one of the most common encephalic lesions found in patients with CP is the PVL (Back and Rosenberg, 2014;Coq et al, 2016). This lesion is characterized by an increase in the size of ventricles associated with a lesion of the surrounding white matter (Hadders-Algra, 2004;Garel and Alberti, 2006;Coq et al, 2008;Clowry et al, 2014).…”
Section: Discussionmentioning
confidence: 70%
“…On the other hand, one of the most common encephalic lesions found in patients with CP is the PVL (Back and Rosenberg, 2014; Coq et al, 2016). This lesion is characterized by an increase in the size of ventricles associated with a lesion of the surrounding white matter (Hadders‐Algra, 2004; Garel and Alberti, 2006; Coq et al, 2008; Clowry et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Uterine artery ligation clearly decreased uterine blood flow and caused fetal weight reduction (29), which resulted in neuronal cell death (30). Further, impaired neuronal cell bodies were observed in the hippocampus and cerebral cortex (31), and were reduced in the entorhinal cortex (32). Hypoxic injury, like uterine artery ligation, was also associated with oligodendrocyte maturation (33) and defects in myelination (34).…”
Section: Discussionmentioning
confidence: 99%